The mental health effects of critical illness insurance: Evidence from China’s aging population - Yuehong Zhang; Manxia Tian; Yumiao Zhang; Wenbin Zang (PLoS ONE, 2025)
Background With the rapid progression of aging, mental health challenges among the elderly have become increasingly pronounced. Addressing these issues is vital for enhancing older adults’ quality of life and maintaining social stability. This study investigates the impact of China’s Critical Illness Insurance (CII) policy, a pivotal component of the national healthcare system, on the mental health of older adults. Methods This study leverages data from the China Health and Retirement Longitudinal Study (CHARLS) and utilizes the staggered implementation of the CII policy across regions as a “quasi-natural experiment.” A multi-period difference-in-differences (DID) approach is employed to estimate the policy’s effects. The analysis focuses on depression tendencies and scores among older adults, controlling for key sociodemographic and economic covariates. Results The findings reveal three key insights: The CII policy significantly reduced depressive tendencies and depression scores among older adults, demonstrating marked improvements in their mental health.The policy effects exhibit substantial heterogeneity, with more pronounced benefits observed among middle- and high-income groups, individuals with chronic illnesses, and older adults in central and western regions.Mechanism analysis indicates that the policy alleviates psychological distress and enhances household financial stability by increasing access to healthcare services, sharing medical expenses, and mitigating financial risks. Conclusion The CII policy has proven effective in improving the mental health of older adults, with significant variations across income levels, health conditions, and regional economic development. By reducing financial stress and improving access to healthcare, the policy not only addresses mental health disparities but also bolsters household economic resilience. These findings underscore the critical importance of tailored health insurance policies to address the diverse needs of an aging population effectively.